2011
DOI: 10.1074/jbc.m111.228379
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic CD38 Protein Forms Intact Disulfides and Is Active in Elevating Intracellular Cyclic ADP-ribose

Abstract: CD38 catalyzes the synthesis of cyclic ADP-ribose (cADPR), a Ca 2؉ messenger responsible for regulating a wide range of physiological functions. It is generally regarded as an ectoenzyme, but its intracellular localization has also been well documented. It is not known if internal CD38 is enzymatically active and contributes to the Ca 2؉ signaling function. In this study, we engineered a novel soluble form of CD38 that can be efficiently expressed in the cytosol and use cytosolic NAD as a substrate to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 54 publications
(42 reference statements)
4
37
0
Order By: Relevance
“…Since the number of positive charges that determine the polarity of membrane protein is equal on each side of the CD38 transmembrane segment, studies from protease digestion [54] and electron microscopy [55] showed that the nuclear CD38 might be a type-Ⅲ membrane protein. Most recently, Zhao et al [56] reported that expression of a cytosolic CD38 protein with deletion of both the N-terminal tail and transmembrane domain results in intact disulfides as well as active enzyme in spite of the cytosolic reductive environment; this result appears to solve the fundamental need of the six disulfides for CD38 enzymatic activity. Based on this finding, they consequently proved the coexpression of type Ⅱ and type Ⅲ CD38 on the surface of leukemia HL-60 cells during retinoic acid-induced differentiation and on interferon Υ-activated natural human monocytes and U937 cells [57] .…”
Section: Topology Of Cd38mentioning
confidence: 99%
“…Since the number of positive charges that determine the polarity of membrane protein is equal on each side of the CD38 transmembrane segment, studies from protease digestion [54] and electron microscopy [55] showed that the nuclear CD38 might be a type-Ⅲ membrane protein. Most recently, Zhao et al [56] reported that expression of a cytosolic CD38 protein with deletion of both the N-terminal tail and transmembrane domain results in intact disulfides as well as active enzyme in spite of the cytosolic reductive environment; this result appears to solve the fundamental need of the six disulfides for CD38 enzymatic activity. Based on this finding, they consequently proved the coexpression of type Ⅱ and type Ⅲ CD38 on the surface of leukemia HL-60 cells during retinoic acid-induced differentiation and on interferon Υ-activated natural human monocytes and U937 cells [57] .…”
Section: Topology Of Cd38mentioning
confidence: 99%
“…It is thus not clear whether type III CD38, with its C-terminal domain inside the cytosol, can actually form the important disulfides and, if not, whether it is still enzymatically functional. The question has been directly addressed by making a soluble CD38 construct containing the C-terminal domain (99). The soluble CD38 directed to express in the cytosol is found to be biologically active in elevating the intracellular cADPR level.…”
Section: Regulation Of Cd38mentioning
confidence: 99%
“…A novel form of CD38 was engineered that expressed efficiently in the cytosol [159]. It was shown that it not only forms intact disulfides but is also fully active in elevating the cytosolic cADPR levels.…”
Section: Membrane Topology and Regulation Of Cd38mentioning
confidence: 99%